Peningkatan Keterampilan Berpikir Komputasional Melalui Penerapan Pembelajaran Berdiferensiasi dengan Model Problem Based Learning - Ndraha, Epifani Diliati; Kamal, Insanul; Octariani , Dhia (LPPM Universitas PGRI Argopuro Jember, 2024)
Computational Thinking Skills are one of the crucial skills in the 21st century, which involve the ability to solve problems systematically and efficiently. This research aims to improve students' computational thinking skills through the application of differentiated learning with the Problem Based Learning (PBL) model in class XII of SMA Negeri 3 Medan. This research uses the classroom action research (PTK) method which consists of three cycles, where each cycle includes planning, implementation, observation and reflection stages. The research results show that the application of the PBL model with a differentiated approach is effective in improving students' computational thinking skills. The average student computational thinking skills test score increased from 52.78% in cycle I to 72.23% in cycle II, and reached 83.34% in cycle III.